A Comparison of Australia, Singapore & Hong Kong Sport Policy: 澳洲、新加坡及香港運動政策的比較 - LAU, Patrick WC; CHAN, Eric CH (Asian Journal of Physical Education & Recreation, 2012)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The present study investigates the sport policy between Australia, Singapore and Hong Kong. The objective is to contrast current Hong Kong sport policy with Australia, Singapore through their respective sport administrative experiences, policy recommendations were made to provide references to the Hong Kong sport policy development in the next decade. The findings demonstrated that Australian and Singapore central sport agencies have worked closely with government departments, national sporting organizations and private sectors to deliver a wide range of sports to their citizens and elite training. Furthermore, based upon the Singapore experience, government’s strategic blueprint and new visions for the future sport development is imperative to the success of sport culture. Finally, sport industry is playing a significant role in both elite and mass sport development. Other policy suggestions are made in the study based upon the lessons from Australia and Singapore. 本文探討了澳洲、新加坡和香港的運動政策。目的是在運動管理系統、運動資金分配、競技運動與大眾運動參與等方面，分別將香港現行的運動政策與澳洲和新加坡的政策進行比較。最後藉著澳洲和新加坡的經驗，對香港未來十年的運動政策發展提出參考性的建議。研究發現澳洲和新加坡的主要管理機構都與政府部門、國家運動單項組織及私人機構長緊密合作，為國民提供了多元化的運動項目選擇和競技訓練。而且，新加坡的經驗進一步顯示政府的長遠規劃和新思維對運動成功發展具決定性影响。最後，運動產業化對競技運動和大眾運動參與的發揮了重要的作用。最後，文中亦基於澳洲和新加坡的經驗提出了其他政策建議。